Development of anti-foulant ultraviolet-assisted polyvinyl alcohol layer on the polysulfone-based nanohybrid membrane for industrial rubber wastewater decontamination - Kusworo, Tutuk Djoko; Kumoro, Andri Cahyo; Aryanti, Nita; Lingga, Fadhilah Fatma; Widiastuti, Ade; Vetcher, Alexandre A.; Dalanta, Febio (Frontiers in Environmental Science, 2023)
Membrane fouling has been reported to be one of the bottlenecks of membrane technologies for wastewater treatment. To mitigate its negative impacts, we fabricated polysulfone membrane (PSf) composite made of silica (SiO2) and graphene oxide (GO) nanoparticles. The composite was further treated by ultraviolet (UV) irradiation and cross-linked with polyvinyl alcohol (PVA) coating to cope with the fouling problem. The modified membrane was applied for industrial rubber wastewater decontamination. The UV irradiation and cross-linked PVA coating to the PSf/GO-SiO2 membrane improved the pseudo-steady state permeate flux by 60.15% from 20.05 to 50.32 L.m-2.h-1 and maintained the permeate flux up to 82.33%. About 85% of total dissolved solids (TDS), 81% of chemical oxygen demand (COD), and 84% of ammonia compound (NH3) with initial concentrations of 335.76, 242.55, 175.19 mg/L, respectively, could be removed after 8 h of membrane treatment. The modified membrane also exhibited an excellent flux recovery ratio up to 83%. The modified membrane can change fouling mechanism from pore blockage to cake filtration, which signifies the capability of the membrane to tackle severe foulants from the membrane’s surface. This implies that incorporating GO/SiO2 nanoparticles with UV irradiation and PVA coating substantially enhanced the physicochemical properties of the PSf membrane.